Dokumentalny świat Andrzeja Wajdy - Mąka-Malatyńska, Katarzyna (Przestrzenie Teorii, 2017)
The article introduces a relatively unknown aspect of Andrzej Wajda’s output – his documentary films. The author examines documentaries on art and autobiographical film, which usually comprise glosses on feature films. These non-fiction films, like Wajda's best-known movies, refer to the codes of Polish culture, created by art and literature, and thanks to which the creative output of the maker of Afterimage (Powidoki) appears to unusually coherent and consistent, regardless of the genealogical classification. The author selects examples to analyse the connections between Wajda’s feature films and the conventions of the documentary. Wajda’s overriding aim in using the poetics of documentary is in each case to undertake mise-en-abîme reflections.